2017
DOI: 10.1186/s13072-017-0132-6
|View full text |Cite
|
Sign up to set email alerts
|

The quest for epigenetic regulation underlying unisexual flower development in Cucumis melo

Abstract: BackgroundMelon (Cucumis melo) is an important vegetable crop from the Cucurbitaceae family and a reference model specie for sex determination, fruit ripening and vascular fluxes studies. Nevertheless, the nature and role of its epigenome in gene expression regulation and more specifically in sex determination remains largely unknown.ResultsWe have investigated genome wide H3K27me3 and H3K9ac histone modifications and gene expression dynamics, in five melon organs. H3K9ac and H3K27me3 were mainly distributed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 102 publications
5
47
0
Order By: Relevance
“…2A ). These observations are consistent with previous studies in angiosperms, moss, and unicellular algae ( Zhang et al , 2007 ; Makarevitch et al , 2013 ; Widiez et al , 2014 ; Baker et al , 2015 ; Hussey et al , 2017 ; Latrasse et al , 2017 ; Mikulski et al , 2017 ; Chica et al , 2017 ; Lü et al , 2018 ; Qi et al , 2018 ; Li et al , 2019 ). This shows that (i) the CUT&RUN method can be successfully applied to large genomes, such as that of Norway spruce, and (ii) despite the significant differences in genome size between angiosperms and gymnosperms, deposition of H3K27me3 is detected in similar genomic features across different plant species.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…2A ). These observations are consistent with previous studies in angiosperms, moss, and unicellular algae ( Zhang et al , 2007 ; Makarevitch et al , 2013 ; Widiez et al , 2014 ; Baker et al , 2015 ; Hussey et al , 2017 ; Latrasse et al , 2017 ; Mikulski et al , 2017 ; Chica et al , 2017 ; Lü et al , 2018 ; Qi et al , 2018 ; Li et al , 2019 ). This shows that (i) the CUT&RUN method can be successfully applied to large genomes, such as that of Norway spruce, and (ii) despite the significant differences in genome size between angiosperms and gymnosperms, deposition of H3K27me3 is detected in similar genomic features across different plant species.…”
Section: Resultssupporting
confidence: 93%
“…So far, most studies in chromatin profiling in plants have been limited to relatively small genomes (e.g. different angiosperms, a moss, and a liverwort) ( Zhang et al , 2007 ; Widiez et al , 2014 ; Hussey et al , 2017 ; Latrasse et al , 2017 ; Chica et al , 2017 ; Lü et al , 2018 ; Montgomery et al , 2020 ). However, genome-wide analysis in gymnosperms has remained a challenge due to the large genome sizes of these species ( Pellicer et al , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We took the sequence of these gene models and compared them to the Melon genome [25] by sequence analysis (Tables S1 and S2; [23,24]). We decided to analyze our data against the melon genome, because there have been several QTL and genomic studies on melon fruit quality that are similar to our study [26][27][28]. Markers associated with fruit flesh color intensity Pumpkin_282381, Pumpkin_93626, Pumpkin_164349, Pumpkin_46427, Pumpkin_210956, and Pumpkin_221779 aligned with pumpkin gene models whose orthologs in melon have been measured to be differentially regulated in green versus orange fruit color [26] and fruit flesh tissue [27].…”
Section: Qtl Mapping and Genomic Analysismentioning
confidence: 93%
“…We decided to analyze our data against the melon genome, because there have been several QTL and genomic studies on melon fruit quality that are similar to our study [26][27][28]. Markers associated with fruit flesh color intensity Pumpkin_282381, Pumpkin_93626, Pumpkin_164349, Pumpkin_46427, Pumpkin_210956, and Pumpkin_221779 aligned with pumpkin gene models whose orthologs in melon have been measured to be differentially regulated in green versus orange fruit color [26] and fruit flesh tissue [27]. In parallel, Pumpkin_164349, which our study showed to be associated with pickleworm tolerance, aligns with CmoCh15G001520, a clathrin heavy chain protein encoding gene orthologous to MELO3C008306 that has been observed to be upregulated in Fusarium infections [28].…”
Section: Qtl Mapping and Genomic Analysismentioning
confidence: 98%